Pure Laparoscopic Donor Hepatectomies: Ready for Widespread Adoption?. Issue 4 (October 2018) - Samstein, Benjamin; Griesemer, Adam; Halazun, Karim; Kato, Tomoaki; Guarrera, James V.; Cherqui, Daniel; Emond, Jean C.
Abstract : Objective: In order to minimize the impact of donation, fully laparoscopic donor hepatectomy (LDH) is being investigated at a few centers throughout the world. We report here our experience with 51 living donor pure laparoscopic hepatectomies. Background: Adoption of minimal access techniques to living donor liver transplantation (LDLT) has been slowed by concerns about donor safety and the quality of the grafts. Methods: Of 344 donor hepatectomies (DHs) for living donor liver transplantation (LDLT) since 1998, 51 pure LDH have been performed since 2009. We report here our experience with 51 living donor pure laparoscopic hepatectomy (LH), based on prospectively collected data. There were 31 left lateral sectionectomy and 20 full lobectomies LH. We matched full lobe LH to open DH prior to introduction of LH. Results: LH increased from 21% of all DH in first 5 years of performing LH to 45% of DH in the most recent 3 years. Laparoscopic donors were more likely female, had lower body mass index, smaller total livers, and smaller allografts but longer operating room times. In the total LD experience, total 5 donors were converted to open surgery (10%), 2 donors required transfusion (4%), and there was 2 donor bile leaks (4%). Recipient patient and graft 1-year survival was 98% and 94%. Conclusions: Our experience indicates that LDH for LDLT can be safely used with appropriate attention to learning curve and progression from left lateral sectionectomy to right hepatectomy.